Digital Marketing for Small and Medium Enterprises (SME) in Jakarta Capital Special Region - Lumbantoruan , Rutman (Universitas Kristen Indonesia, 2022)
The DKI Jakarta government socializes and facilitates improvements in welfare through small and medium enterprises (SME) activities in Jakarta. Digital marketing breakthroughs are one effort to increase the pace of the economy for the residents of Jakarta. So, it is hoped that SME can adapt to Era Society 5.0. This system was created to accelerate the implementation of small and medium enterprises (SME) and collaborate with fellow entrepreneurs practicing the digital marketing information system.